2006
DOI: 10.1016/j.jmatprotec.2006.07.009
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of tool wear and cutting force variation in the end milling of Inconel 718 with coated carbide inserts

Abstract: Inconel 718 is a difficult-to-cut nickel-based superalloy commonly used in aerospace industry. This paper presents an experimental study of the tool wear propagation and cutting force variations in the end milling of Inconel 718 with coated carbide inserts. The experimental results showed that significant flank wear was the predominant failure mode affecting the tool life. The tool flank wear propagation in the up milling operations was more rapid than that in the down milling operations. The cutting force var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(99 citation statements)
references
References 10 publications
(13 reference statements)
2
96
0
1
Order By: Relevance
“…The hardness of the AlCrMoTi (#4) and AlCrMoTiV (#7) solid solutions were compared with that of other HEAs and commercial alloys and is summarized in Table 2 [26][27][28][29][30][31]. The hardness of the AlCrMoTi (#4) and AlCrMoTiV (#7) were 606 ± 11 and 556 ± 25 HV, respectively.…”
Section: Specific Hardness Of the Al-ti-containing Heasmentioning
confidence: 99%
“…The hardness of the AlCrMoTi (#4) and AlCrMoTiV (#7) solid solutions were compared with that of other HEAs and commercial alloys and is summarized in Table 2 [26][27][28][29][30][31]. The hardness of the AlCrMoTi (#4) and AlCrMoTiV (#7) were 606 ± 11 and 556 ± 25 HV, respectively.…”
Section: Specific Hardness Of the Al-ti-containing Heasmentioning
confidence: 99%
“…When end milling of Inconel 718 using coated carbide tool, force variation ranges overlapped between successive cuttings passes (Li et al, 2006). Along with the tool wear propagation in successive cutting passes, the overall trend of the main peak values in the X-, Y-, and Z-directions for both the down and up milling operations was in a gradual increase.…”
Section: Introductionmentioning
confidence: 95%
“…Although the cutting speeds were maintained at 150 m /min but the longest tool life was obtained at 90 m/min with TiAlN coatings, thus explaining the crucialness of the choice of coating to influence the tool life [7]. Li et al (2006), conducted experiments to study the tool wear propagations and cutting force variations in the end milling of inconel 718. They found that the initial flank wear was the main factor in effecting the tool life.…”
Section: Introduction and Literature Surveymentioning
confidence: 99%
“…They found that the initial flank wear was the main factor in effecting the tool life. The analysis on cutting forces performed showed that the thermal effects were the main reasons for the peak force variation within a single pass [8]. Krain et al (2007) tried to optimize the tool life and productivity while milling of inconel 718.…”
Section: Introduction and Literature Surveymentioning
confidence: 99%